2014
DOI: 10.1097/acm.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

The Harvard Medical School Academic Innovations Collaborative

Abstract: The AIC model shows promise as a path for AMCs to catalyze health system transformation through primary care improvement. In addition to further evaluating the impact of practice transformation, expansion will require support from AMCs and payers, and the application of similar approaches on a broader scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 4 publications
2
42
0
Order By: Relevance
“…Meets quarterlyMission statement: “To establish a patient advocate forum to gain quality experiences, observations, and suggestions for improvement”Activities: review practice improvement project for depression care management; provide insights on scaling patient action group to entire Rochester, MN primary care practiceProduced more patient-centered, personal-handoff process and associated provider scripting (e.g., from “someone will call you” to “the care manager is an RN who works with me”). Enrollment of patients diagnosed with depression into care management intervention was 96.5% Baker et al [29]US CareSouth outpatient clinicsEducational material design around body mass index after negative initial feedback regarding topic approach; revised pain assessment“A strong collaborative engagement with the patient is likely necessary to achieve high reliability” Bitton et al [27]Hospital- and community-based primary care teaching practices affiliated with Harvard Medical SchoolClinic “transformation teams” encouraged to include patients as core members“Trainees and patients can be agents of change, and their presence provides added motivation for academic faculty to create and support change” Coulter and Elwyn [20]UK policy efforts to involve public in healthcare processesCommunity-health councils, proposed statutory patient forums and commission for patient and public involvement and health, patient advisory and liaison services in each trust, annual patient surveyNo empirical findings reported DiGioia et al [23]University of Pittsburgh Medical Center, US6-step patient- and family-centered care methodology including using Codesign Toolkit and Improvement Team to close gaps between current and ideal care experiences“Refocuses existing resources around the patient and family rather than fitting patients and families around the physician and system. It makes it possible to take any current state and move the care experience toward the ideal—as defined by patients and families” Fontaine et al [28]Minnesota primary care practicesState PCMH certification standard development included patient-advocacy representatives; published standards include “continuous improvement process that included a quality-improvement committee with active patient recruitment and participation”Patient’s positive experiences with PCMH increased practice leaders’ job satisfaction and trust in the processProcess for using patients as PCMH advisors/getting input on PCMH changes from patient partners on change team all correlated significantly ( P  ≤ 0.01) with practice system change (but not clinical outcomes) [33] Karazivan et al [24]Direction of Collaboration and Patient Partnership at the University of Montreal: Implemented by two primary care teams as of 2014<...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meets quarterlyMission statement: “To establish a patient advocate forum to gain quality experiences, observations, and suggestions for improvement”Activities: review practice improvement project for depression care management; provide insights on scaling patient action group to entire Rochester, MN primary care practiceProduced more patient-centered, personal-handoff process and associated provider scripting (e.g., from “someone will call you” to “the care manager is an RN who works with me”). Enrollment of patients diagnosed with depression into care management intervention was 96.5% Baker et al [29]US CareSouth outpatient clinicsEducational material design around body mass index after negative initial feedback regarding topic approach; revised pain assessment“A strong collaborative engagement with the patient is likely necessary to achieve high reliability” Bitton et al [27]Hospital- and community-based primary care teaching practices affiliated with Harvard Medical SchoolClinic “transformation teams” encouraged to include patients as core members“Trainees and patients can be agents of change, and their presence provides added motivation for academic faculty to create and support change” Coulter and Elwyn [20]UK policy efforts to involve public in healthcare processesCommunity-health councils, proposed statutory patient forums and commission for patient and public involvement and health, patient advisory and liaison services in each trust, annual patient surveyNo empirical findings reported DiGioia et al [23]University of Pittsburgh Medical Center, US6-step patient- and family-centered care methodology including using Codesign Toolkit and Improvement Team to close gaps between current and ideal care experiences“Refocuses existing resources around the patient and family rather than fitting patients and families around the physician and system. It makes it possible to take any current state and move the care experience toward the ideal—as defined by patients and families” Fontaine et al [28]Minnesota primary care practicesState PCMH certification standard development included patient-advocacy representatives; published standards include “continuous improvement process that included a quality-improvement committee with active patient recruitment and participation”Patient’s positive experiences with PCMH increased practice leaders’ job satisfaction and trust in the processProcess for using patients as PCMH advisors/getting input on PCMH changes from patient partners on change team all correlated significantly ( P  ≤ 0.01) with practice system change (but not clinical outcomes) [33] Karazivan et al [24]Direction of Collaboration and Patient Partnership at the University of Montreal: Implemented by two primary care teams as of 2014<...>…”
Section: Resultsmentioning
confidence: 99%
“…Many articles reported that patient/family partnerships resulted in process improvements, including staff trainings [22, 26], service redesign [16, 17, 21, 27, 28], and patient materials (e.g., for self-management or new patient orientation) [18, 2931]. Several articles said patient/family involvement catalyzed practice improvement through “influential stories,” “different perspectives” [26] or “experiential knowledge” [32].…”
Section: Resultsmentioning
confidence: 99%
“…Just avoid repelling them.^Building excellence in primary care is certainly easier when the institutional culture values this field, but a supportive institutional culture is not necessary if deans, department 10 4 Create strategic educational alliances with local practices, organizations, and groups that have or seek to develop highperformance primary care services. 68 5 Support primary care teaching faculty. ‡ 6 Put student and resident education in primary care on an equal footing.…”
Section: Resultsmentioning
confidence: 99%
“…If sufficient community-based practices are not available, the solution may be community engagement to support local practice innovation. 68 As schools become or join accountable care organizations, they may be able to shift funds to support primary care.…”
Section: Commonly Discussed Solutions To the Adult Primary Care Physimentioning
confidence: 99%
“…A learning climate may be present, which is associated with more successful implementation of new practices (Britton et al, 2014;Damschroder et al, 2009). …”
Section: Discussionmentioning
confidence: 98%